2011
DOI: 10.1103/physreva.84.022506
|View full text |Cite
|
Sign up to set email alerts
|

Casimir repulsion in moving media

Abstract: Casimir-Lifshitz interaction emerging from relative movement of layers in stratified dielectric media (e.g., non-uniformly moving fluids) is considered. It is shown that such movement may result in a repulsive Casimir-Lifshitz force exerted on the layers, with the simplest possible structure consisting of three adjacent layers of the same dielectric medium, where the middle one is stationary and the other two are sliding along a direction parallel to the interfaces of the layers.Comment: 22 pages, 10 figure

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 39 publications
3
32
0
Order By: Relevance
“…From previous studies [7,[13][14][15], it is known that the electromagnetic field in moving media is subject to the canonical quantization; therefore, we may find the zero-point energy of the quantum-electromagnetic fluctuations in the waveguide shown in Fig. 1 (at zero temperature) with the standard summation over the eigenfrequencies of all possible electromagnetic modes in this structure.…”
Section: Zero-point Energy and Casimir's Force At Zero Temperaturementioning
confidence: 99%
See 3 more Smart Citations
“…From previous studies [7,[13][14][15], it is known that the electromagnetic field in moving media is subject to the canonical quantization; therefore, we may find the zero-point energy of the quantum-electromagnetic fluctuations in the waveguide shown in Fig. 1 (at zero temperature) with the standard summation over the eigenfrequencies of all possible electromagnetic modes in this structure.…”
Section: Zero-point Energy and Casimir's Force At Zero Temperaturementioning
confidence: 99%
“…However, we do not consider velocities above the Cherenkov threshold to avoid any potential instabilities related to the appearance of negative quanta [7] in media moving with such high velocities.…”
Section: The Waves In a Waveguide Filled With A Moving Mediummentioning
confidence: 99%
See 2 more Smart Citations
“…This force acts against the movement of the bodies, and, thus, it is tempting to imagine that there is a certain "viscosity" associated with the fluctuating field 3 that persists even at T = 0 K. It was recently found that the normal Casimir forces are also affected by the shear movement of the bodies. 23 Although this picture is very intuitive, it is not immediately evident how such a nonreversible and nonconservative effect as friction may result out of the mentioned quantummechanical model. Indeed, in quantum electrodynamics it is typically assumed that the fluctuating electromagnetic field, together with the particles that interact with it, is captured within an adiabatically closed cavity.…”
Section: Introductionmentioning
confidence: 95%